(untitled) (Agro Productividad, 2024)
Objective: This study aimed to evaluate the biodiversity in postharvest fruit quality and photosynthetic attributes of eight native tomato varieties compared to two commercial hybrids. Design/Methodology/Approach: A randomized complete block design with four replicates and four plants per plot was used to allocate treatments. Statistical analysis was conducted with SAS 9.4 using analysis of variance (ANOVA) and mean comparison of by Tukey (p≤0.05). Results: Varietal diversity in transpiration rate (E) was detected, but not in net photosynthetic rate (A) nor in water use efficiency (WUE). The Oax-131 variety stood out for its high photosynthetic parameters, such as Amax, for its saturation point, and for having carboxylation efficiency similar to the El Cid® hybrid. In terms of fruit weight loss postharvest, five native varieties had losses below the conventional limit of 7%, while the Oax-131 variety-maintained firmness similar to the hybrids during the first 6 days. Study Limitations/Implications: The study was limited to eight native varieties and the diversity measured in gas exchange rates and photosynthetic parameters may not represent all native varieties. Findings/Conclusions: The native Oax-131 variety excelled in photosynthetic traits and postharvest quality, demonstrating equal or superior performance compared to commercial hybrids.